Milk thistle impedes the development of carbontetrachloride-induced liver damage in rats through suppression of bcl-2 and regulating caspase pathway - Aslan, Abdullah; Can, Muhammed Ismail (Pergamon-Elsevier Science Ltd, 2014)
Aim: The objective of this study was to examine whether MT plays a protective role against the damage in the liver by administering carbontetrachloride (CCl4) to rats. Main method: 28 male Wistar albino (n = 28, 8 weeks old) rats have been used in the study. The rats were distributed into 4 groups according to their live weights. The groups were: (i) negative control (NC): normal water consuming group to which no CCl4 and milk thistle (MT) is administered; (ii) positive control (PC): normal water consuming group to which no Cat is administered but MT is administered; (iii) CCl4 group: normal water consuming and group to which CCl4 is administered (2 ml/kg live weight, ip); and (iv) CCl4 + MT group: CCl4 and MT administered group (2 ml/kg live weight. ip). Caspase-3, caspase-9, bax, and bcl-2 protein syntheses were examined via western blotting. MDA determination in liver tissue was made using spectrophotometer. Key findings: MDA amount has decreased in the CCl4 + MT group in comparison to CCl4 group whereas caspase-3 and caspase-9 has increased and bax and bcl-2 has decreased. Significance: These results show that MT protects the liver against oxidative damage. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Milk thistle; Liver damage; Caspase-3; Caspase-9; Bax; Bcl-2